2009
DOI: 10.1002/cphc.200800699
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CF Bonds with Multiple‐Bond Character: Bond Lengths, Stretching Force Constants, and Bond Dissociation Energies

Abstract: Isoelectronic C=F(+) and C=O bonds contained in fluoro-substituted carbenium ions, aldehydes, and ketones are investigated with regard to their bond properties by utilizing the vibrational spectra of these molecules. It is demonstrated that bond dissociation energies (BDEs), bond lengths, vibrational stretching frequencies, and bond densities are not reliable descriptors of the bond strength. The latter is related to the intrinsic BDE, which corresponds to nonrelaxed dissociation products retaining the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 74 publications
(58 reference statements)
5
83
0
Order By: Relevance
“…This result was contrasted by an investigation of Ohno and coworkers (entry 61), who could derive a simplified Badger-type equation by using effective bond lengths in the study of 74 CX bonds (X¼C, Si, Ge, N, P, As, O, S, Se, F, Cl, Br) contained in polyatomic molecules. Kraka and Cremer [67] made a similar observation when investigating some 46 isoelectronic CO and CF þ bonds. For the purpose of resolving these contradictory claims on the applicability of the Badger-Herschbach-Laurie equations between bond length and bond stretching force constant, there is the need to reinvestigate the physical basis of Badger-type relationships and to obtain a reliable assessment of their predictive value.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…This result was contrasted by an investigation of Ohno and coworkers (entry 61), who could derive a simplified Badger-type equation by using effective bond lengths in the study of 74 CX bonds (X¼C, Si, Ge, N, P, As, O, S, Se, F, Cl, Br) contained in polyatomic molecules. Kraka and Cremer [67] made a similar observation when investigating some 46 isoelectronic CO and CF þ bonds. For the purpose of resolving these contradictory claims on the applicability of the Badger-Herschbach-Laurie equations between bond length and bond stretching force constant, there is the need to reinvestigate the physical basis of Badger-type relationships and to obtain a reliable assessment of their predictive value.…”
Section: Introductionmentioning
confidence: 67%
“…Instead, there is the need for local mode information that provides bond stretching frequencies or force constants, which are no longer contaminated by contributions from other vibrational modes. For the purpose of clarifying the relationship between delocalized normal and local internal coordinate modes, we present here the theory of the adiabatic internal coordinate modes (AICoMs), recently used to set up bond length-bond stretching force constant relationships by Kraka and Cremer [67]. The standard method for calculating the vibrational spectra of polyatomic molecules with K atoms is based on two major approximations [73,74].…”
Section: Dissection Of a Polyatomic Molecule Into A Collection Of Quamentioning
confidence: 99%
See 1 more Smart Citation
“…The force constant k a of an AB stretching mode (A and B being bonded) is a reliable measure for the AB bond strength [132][133][134][135]. This does not hold for the local frequency ω a which depends also on the masses of atoms A and B thus disguising the electronic origin of the bond strength.…”
mentioning
confidence: 98%
“…One of the most useful applications is the analysis of bond dissociation energy. In fact, bond dissociation energy has been analyzed to understand the bond strength, bond character, and reactivity [126,127,128,129,130,131,132,133,134,135]. It was found that the C–F bond is relatively stronger than C–H.…”
Section: Chemical Degradation Mechanism Studied By Theoretical Metmentioning
confidence: 99%